The place of the State Bureau of Investigation in the system of state law enforcement agencies of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article describes the place of the State Bureau of Investigation in the system of state bodies of Ukraine, in particular, the content of the categories “state bodies” and “public authorities” is defined, the system of state bodies is outlined, and the specifics of law enforcement agencies are clarified. It is noted that state bodies (public authorities) are characterised by their own specific features, among which the following are distinguished: a set of state bodies form the apparatus of the State, and therefore each of them is one of the elements of the integral system of the State apparatus; they are created and operate on the basis of relevant regulations, in the person of one person (citizen) or a group of citizens; each structural unit (state body) is endowed with unique powers of state power; they are created with the aim of performing tasks and It is also emphasised that the State Bureau of Investigation is a law enforcement agency.Therefore, the place of the State Bureau of Investigation in the system of state bodies is determined by its legal status as a central executive body, as evidenced by the specifics of its activities, since it was established for the special purpose of preventing and combating crimes committed by special categories of subjects, as well as war crimes, which is consistent with the law enforcement function of the state and has nothing to do with either legislative or judicial activities; as a law enforcement agency in view of the fact that its main and, in fact, the only task is to counteract criminal offences within its competence; as a state body with a special status, as evidenced by its tasks, powers and the fact that it carries out its activities independently and independently of other executive authorities in the organisational and functional aspect.
Keywords: State Bureau of Investigation; law enforcement agencies; state bodies; public authorities; central executive body; special status.